ANALISIS DAN DESAIN SISTEM PRODUKSI KEMASAN AKTIF ANTIMIKROBA UNTUK MENJAGA MUTU PRODUK PANGAN - Reskiati Wiradhika Anwar (AGROINTEK, 2023)
Development of antimicrobial active packaging has much to do with different types of raw materials, carrier antimicrobial agent, even to the development of methods that aim to maximize the function of the packaging to be applied to food products. However, the diversity of application of antimicrobial packaging makes packaging products not specific results to be used. Based on these problems, there should be analysis and design that aims to produce models of the incorporation of elements of the matrix constituent antimicrobial packaging, films, and antimicrobial compounds, and can provide more benefits to consumers of the safety and quality of food products are packaged. Modeling tested as a real simulation system. The method used by the analysis of the needs of the production, use case, PHD, BPD and BPMN, then the system design verification and validation will be done in analyzing the system contained in an antimicrobial packaging production systems. And also used the formulation of Association Rules Mining in designing a system to achieve the goal of the acquisition of rules that interpret the relationship between changes in product quality paprika with contamination that appears in the product as a reference to the influence of active packaging antimicrobial produced by the connection of incorporation is done in the production stage. To maintan the qualitu of packaged food products, a system of linkages was created between the incorporation processes in the production of antimicrobial packaging.